Volunteerism in the system of human self‐realization: problems of finding a balance between public and personal interests - G.S. Kalyanova (Векторы благополучия: экономика и социум)
Relevance. Active participation in the volunteer movement is one of the conditions for a person's self‐realization in modern society. Volunteer activity contains a wide variety of opportunities and forms of human self‐realization through independent or organized involvement in solving socially significant issues. Despite the rather large potential of volunteerism in Russia, the real situation shows that there are many problems. Of particular importance in their solution is the search for a balance between personal and public interest in determining the need to participate in volunteer activities. Aim. To substantiate the importance of achieving a balance of public and personal interests in human self‐realization through participation in active forms of volunteerism. Methods. Comparative method, logical and systematic analysis, statistical method based on data contained on the websites of the Ministry of Economic Development, Rosstat, on the Dobro website, according to the results of surveys conducted by All‐Russian Center for the Study of Public Opinion, Higher School of Economics, Public Opinion Foundation, etc. Result. It is concluded that it is necessary to improve the system of volunteering system based on the formation of conditions for sustainable motivation and expansion of active forms of volunteer activity. It is necessary to abandon the predominant popularization of volunteering through mass events. The transition from a neutral or passive positive attitude to real participation in volunteerism programs presupposes the formation of each person's own idea of the balance of public and personal interests. This will allow for a transition from emotional motivation for one‐time participation in volunteer activities to the formation of sustainable motivation and intolerance of an indifferent attitude to "other people's pain".